2018
DOI: 10.3389/fpls.2018.00864
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Demarcation of Setaria pumila (Poir.) Roem. & Schult., S. verticillata (L.) P. Beauv., and S. viridis (L.) P. Beauv. (Cenchrinae, Paniceae, Panicoideae, Poaceae) From Phytolith Signatures

Abstract: Background and Aims: The role and significance of phytoliths in taxonomic diagnosis of grass species has been well documented with a focus on the types found in foliar epidermis and the synflorescence. The present paper is an attempt to broaden the scope of phytoliths in species diagnosis of grasses by developing phytolith signatures of some species of the foxtail genus Setaria P. Beauv. through in situ location and physico-chemical analysis of various phytolith morphotypes in different parts of the plant body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 189 publications
(234 reference statements)
0
3
0
Order By: Relevance
“…Long (elongate lobated) and short (crosses) cell phytoliths from Panicoideae were also observed together with silica skeletons with long cells with Ո and ƞ ornamentations. These types of ornamentation are normally found in Panicoideae and other C₄ grasses inflorescence [ 47 , 177 180 ] and more specifically Setaria verticillata ( Fig 10 ). For this reason, we made morphometric comparisons (based on characters from Zhang et al [ 125 ] between Ո patterns from modern Setaria verticillata from our reference collection and the recovered archaeological material showing similar patterns.…”
Section: 0 Resultsmentioning
confidence: 99%
“…Long (elongate lobated) and short (crosses) cell phytoliths from Panicoideae were also observed together with silica skeletons with long cells with Ո and ƞ ornamentations. These types of ornamentation are normally found in Panicoideae and other C₄ grasses inflorescence [ 47 , 177 180 ] and more specifically Setaria verticillata ( Fig 10 ). For this reason, we made morphometric comparisons (based on characters from Zhang et al [ 125 ] between Ո patterns from modern Setaria verticillata from our reference collection and the recovered archaeological material showing similar patterns.…”
Section: 0 Resultsmentioning
confidence: 99%
“… Desai et al (2018) established S. viridis as a model system to uncover the mechanism underlining the Time of Day of Anther Appearance (TAA) regulation. In situ localization study of phytoliths exhibited species-specific morphotypes in different tissues of Setaria species that could be used for taxonomic characterization of Setaria ( Bhat et al, 2018 ). Root microbiome examination of foxtail millet plants sampled from two geographically isolated locations indicated that the host plant assists the growth of specific bacteria in the rhizosphere ( Jin et al, 2017 ).…”
Section: Omics Resources In Setariamentioning
confidence: 99%
“…Netolitsky (1929) revised phytolith morphotypes and attempted to identify marker phytolith morphotypes in different taxa of flowering plants. Subsequently, phytolith characteristics were used effectively by several authors in the characterization and identification of different members of grasses (Rosen 1992;Wang and Lu 1993;Pearsall et al 1995;Houyouan et al 1997;Zhao et al 1998;Fahmy 2008;Shakoor et al 2014), Mudassir et al (2018) effectively and efficiently used phytolith signatures (elemental composition) to identify three species of Setaria (Poaceae), Prychid et al (2004) summarized the silica morphotypes in the tribe Cypereae of the subfamily Cyperoideae and in the tribe Cariceae of the subfamily Caricoideae. Though, Muasya et al (2009) divided the family Cyperaceae into two subfamilies: Cyperoideae and Mapanioideae, based on molecular data.…”
Section: Introductionmentioning
confidence: 99%